2012
DOI: 10.1021/ja304929h
|View full text |Cite
|
Sign up to set email alerts
|

Where’s the Charge? Protonation Sites in Gaseous Ions Change with Hydration

Abstract: The role of water in stabilizing sites of protonation in small gaseous ions is investigated using electrospray ionization (ESI) coupled with infrared photodissociation spectroscopy and computational chemistry. Protonation of p-aminobenzoic acid (PABA) and p-aminobenzoic acid methyl ester (PABAOMe) occurs at the carbonyl oxygen atom both in isolation and when one water molecule is attached. However, protonation occurs at the amine nitrogen atom, which is the most favorable site in aqueous solution, for PABAOMeH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
161
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(173 citation statements)
references
References 57 publications
11
161
1
Order By: Relevance
“…This marks the onset of solution phase properties with respect to basicity. This finding is supported by an earlier IR photodissociation spectroscopy/computational study [64] that demonstrated that when fewer than 6 H 2 O molecules were bound to 4-ABA•H + , the O-protonated tautomer was more stable and abundant. However, with 6 and more H 2 O molecules, the Nprotonated tautomer (i.e., the more stable tautomer in protic liquid) was more stable and abundant.…”
Section: Resultssupporting
confidence: 63%
“…This marks the onset of solution phase properties with respect to basicity. This finding is supported by an earlier IR photodissociation spectroscopy/computational study [64] that demonstrated that when fewer than 6 H 2 O molecules were bound to 4-ABA•H + , the O-protonated tautomer was more stable and abundant. However, with 6 and more H 2 O molecules, the Nprotonated tautomer (i.e., the more stable tautomer in protic liquid) was more stable and abundant.…”
Section: Resultssupporting
confidence: 63%
“…Based on IM and MS/MS data, they conclude that these ions only differ in the site of protonation, and are thus referred to as "protomers". Other studies have reported on the observation of protomers for different analytes using both MS as well as other techniques such as gas-phase infrared photodissociation (IRPD) spectroscopy [56][57][58]. We also explain the observation here of two drift times for melphalan by the presence of charge isomers (protomers) in the gas phase [26].…”
Section: Observation Of Multiple Drift Times For Melphalansupporting
confidence: 58%
“…In particular,t he competition between the possible water-binding sites (NH 3 + , COOH)h as thoroughly been exploredt hrough the examples of protonated phenylalanine, [29] valine, [30] glycine, [31] tryptophan, [32,33] and tyrosine. [33] Hydration can also influence the protonation site [34][35][36] and, similar to the neutrals pecies, also the conformation of protonated biomolecules. [37][38][39][40] In contrast to amino acids, no spectrali nformation is availablef or H + PEA-(H 2 O) n clusters and related microhydrated protonated aromatic ethylamino neurotransmitters.…”
Section: Introductionmentioning
confidence: 99%